Mechanical and chemical properties of rotator cuff tendons - Chaudhury, US (2011)
Shoulder disease is the third most common musculoskeletal problem, and rotator cuff tendon tears account for the greatest proportion of shoulder complaints. Rotator cuff tears are estimated to affect between 5-30% of adults, with higher incidences of tearing and failure to heal in elderly patients, placing a huge socioeconomic burden on an ageing British population. Serious concern arises as a large proportion of technically correct surgical repairs re-rupture. The intra-articular environment of the tendon often precludes normal healing and surgical repair is often necessary to improve pain and restore some function. It is feasible that there may be an inherent physiological or biomechanical defect in the tissue that prevents complete healing without some further augmentation to the surgical repair. Improved understanding of the biochemical and biomechanical changes in torn rotator cuff tendons may help to reduce the high rerupture rates. This study aimed to characterise normal, and different sized rotator cuff tendon tears from small samples obtained intraoperatively to try to use tests that may potentially be clinically useful in the future.